2020
DOI: 10.20944/preprints202011.0302.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Single-Celled Ancestors of Animals: A History of Hypotheses

Abstract: Animals, with their complex and obligate multicellularity, evolved from microbial eukaryotes that were likely obligately or facultatively unicellular. The nature of the unicellular progenitors of animals has intrigued biologists since the late 19th century, coinciding with the parallel spread of the cell theory and the theory of evolution. However, views on the ancestry of animals have been extremely varied. The huge diversity of single-celled organisms, the tremendous plasticity of animal cellular phenotypes,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 89 publications
1
12
0
Order By: Relevance
“…Metazoans are widely thought to be the descendants of a colony of cells similar to modern choanoflagellates 109 , 125 , although alternative scenarios also have been proposed 111 , 112 , 126 . The genomes of the ancestral cells likely contained the large set of genes shared between Metazoa and Holozoa, including some that are absent in modern choanoflagellates 110 , 112 , 127 .…”
Section: Discussionmentioning
confidence: 99%
“…Metazoans are widely thought to be the descendants of a colony of cells similar to modern choanoflagellates 109 , 125 , although alternative scenarios also have been proposed 111 , 112 , 126 . The genomes of the ancestral cells likely contained the large set of genes shared between Metazoa and Holozoa, including some that are absent in modern choanoflagellates 110 , 112 , 127 .…”
Section: Discussionmentioning
confidence: 99%
“…Animals are also proposed to have evolved via juvenile characters (by paedomorphism) from an organism that resembled a planula, i.e. , a cnidarian larva [ 36 ]. Others suggested that animals derived from an amorphous collection of cells with a gradually developing internal cavity that gave birth to primitive sponge like or a cnidaria-like animal [ 37 ].…”
Section: Models For the Rise Of Multicellularitymentioning
confidence: 99%
“…Then, based on the resemblance between choanoflagellates and the choanocytes of sponges, animals were thought to derive from a colony of cells similar to choanoflagellates [35]. Animals are also proposed to have evolved via juvenile characters (by paedomorphism) from an organism that resembled a planula, i.e., a cnidarian larva [36]. Others suggested that animals derived from an amorphous collection of cells with a gradually developing internal cavity that gave birth to primitive sponge like or a cnidaria-like animal [37].…”
Section: Leading To Animalsmentioning
confidence: 99%
“…Nonetheless, the origin of animal amoeboid cells has remained mysterious ( Fritz-Laylin, 2020 ), in part because the closest living relatives of animals, the choanoflagellates ( Ruiz-Trillo et al, 2008 ; King et al, 2008 ), have been thought to exist solely in a flagellate form (except while encysted [ Leadbeater, 2015 ]). The nature of the protozoan ancestor of animals was a matter of debate as early as the 19th century, when the relationship between animals and choanoflagellates was still unknown (reviewed in Brunet and King, 2020 ). Haeckel originally proposed in 1874 that animals descended from amoebae that evolved coloniality and later acquired cilia ( Haeckel, 1874 ).…”
Section: Introductionmentioning
confidence: 99%